CAPOEIRA Structuration as Physical Education content in elementary and high school - Sérgio Augusto Rosa de Souza; Amauri Aparecido Bássoli de Oliveira (Journal of Physical Education (Maringá), 2008)
Capoeira was born in the senzalas (plantation slave quarters) and was created as a dominated class' fight against the existing slavery system. The capoeira suffered persecution and, at ideological resistance level, troubled the dominant culture codes for many years. Nowadays it is studied by different social segments through the world, being a reality its practice in elementary school, high school and college. However, it isn't deeply studied or grounded in its technical and cultural structure yet for school use. This study aims to structure capoeira as a content for physical education at elementary and high school. The initial part of this work tries to introduce and justify the capoeira as a content to be used in school. The second part introduces some capoeira's aspects that must be observed in physical education, which is allowed by the authors proposed structuring. Finally, there is a scheme of a capoeira class for the first year of elementary school, based on an open proposal, intending to discuss pedagogical action.